The family Law developments in the case: “Sons of Ricardo Moran” - Portilla Cortez, Melistsen Abigail (2024)
Law evolves in response to changes in society over time, ensuring that laws are relevant and effective in a constantly changing society. However, the Peruvian case is particular because it is still reluctant to new family structures, as initially occurred with Ricardo Moran and his single-parent family, but which was corrected by the Constitutional Court, with its recent ruling in Case No. 00882-2023-PA/TC, ordering the recognition of Peruvian nationality to the children of Ricardo Moran, conceived under Assisted Human Reproduction Techniques in the United States. In this way, the present work is introduced to the analysis of the implications of this decision for the Family Law, starting from guarantees such as equality and nondiscrimination, leading us to review the Constitutional Law to evaluate the possible limits and benefits of what the Supreme interpreter of the Magna Carta ordered.